Detection and characterization of eravacycline heteroresistance in clinical bacterial isolates - Zhang, Yingfeng; Liu, Dongdong; Liu, Yongzhu; Li, Qiwei; Liu, Hongwei; Zhou, Peng; Liu, Yaqin; Chen, Lili; Yin, Weiguo; Lu, Yang (Frontiers in Microbiology, 2024)
Eravacycline (ERV) has emerged as a therapeutic option for the treatment of carbapenem-resistant pathogens. However, the advent of heteroresistance (HR) to ERV poses a challenge to these therapeutic strategies. This study aimed to investigate ERV HR prevalence among common clinical isolates and further characterize ERV HR in carbapenem-resistant Klebsiella pneumoniae (CRKP). A total of 280 clinical pathogens from two centers were selected for HR and analyzed using population analysis profiling (PAP) and modified E-tests. The PAP assay revealed an overall ERV HR prevalence of 0.7% (2/280), with intermediate heterogeneity observed in 24.3% (68/280) of strains.The proportion of heteroresistant strains was 18.3% according to modified E-test results. A timekilling assay demonstrated that CRKP CFU increased significantly after 10 hours of ERV treatment, contributing to the reduced bactericidal effect of ERV in vitro. Interestingly, dual treatment with ERV and polymyxin B effectively inhibited the total CFU, simultaneously reducing the required polymyxin B concentration. Furthermore, fitness cost measurements revealed a growth trade-off in CRKP upon acquiring drug resistance, highlighting fitness costs as crucial factors in the emergence of ERV HR in CRKP. Overall, the findings of the current study suggest that ERV HR in clinical strains presents a potential obstacle in its clinical application.